Navigating educational transformation: Understanding learning styles’ preferences of Egyptian students in the post-pandemic era - Morsi, Wesam (Edelweiss Applied Science and Technology, 2025)
This study investigated the Learning style preferences of Egyptian EFL learners post-COVID-19. It aims to examine differences emerging in multimodal and bimodal learning preferences based on demographic variables of age and gender and consider the cultural educational context in Egypt during and post the pandemic era. Utilizing the VARK Model, Mayor’s Multimodal Learning Theory, and the Connectivism Learning Theory a survey comprising 19 questions was disseminated to 211 Egyptian EFL students from various age groups. Findings reveal a predominant preference for multimodal learning, particularly visual and read/write styles, with significant variations between genders. Female learners exhibited a stronger inclination towards kinesthetic styles, while males preferred visual methods. Younger learners and female students showed a stronger preference toward the multimodal approach that integrates technology-mediated learning, whereas older students and male learners were in favor of the more traditional modes of learning. The study highlights the importance of integrating traditional instruction wit multimedia resources, particularly for younger learners who thrive in interactive settings. Recommendations include encouraging collaboration between public and private educational sectors, increase the community services and initiatives for community-based learning to address the diverse needs of unprivileged learners. The study advocates for an innovative and holistic teaching approach to enhance engagement and motivation, achieve quality education, and cultivate an informed, skilled generation capable of contributing to the sustainable future of Egypt 2030.